Integrative scRNA-seq and transcriptomic analysis initially reveals monocyte/macrophage activation drives EV-A71-induced immune dysregulation and neural injury in severe HFMD - Wang, Muqi; Zhang, Meng; Deng, Huiling; Zhang, Yufeng; Liu, Chenrui; Chen, Yuan; Zhang, Chuting; Zhang, Wen; Jia, Xiaoli; Dang, Shuangsuo; Li, Yaping (Frontiers in Immunology, 2025)
ObjectiveEnterovirus 71 (EV-A71) is a major pathogen of severe hand, foot and mouth disease (HFMD) in children, but the mechanism by which it develops into severe HFMD remains unclear, especially the role of macrophage-mediated immune dysregulation.MethodsBioinformatics tools were utilized to analyze the transcriptome sequencing results of peripheral blood monocytes (PBMCs) infected with different titers of EV-A71 at various time points. Single-cell sequencing technology was used to sequence obtained PBMCs from a severe HFMD patient due to EV-A71 and a healthy control. Macrophages infected with EV-A71 were collected for transcriptomic analysis, and were indirectly co-cultured with nerve cells to observe their inhibitory effects on nerve cells.ResultsSingle-cell RNA sequencing (scRNA-seq) revealed that EV-A71 infected severe HFMD patient had higher monocyte and macrophage ratio (18.50% vs. 8.85%), especially classical (64.59% vs. 57.24%) and non-classical (32.23% vs. 23.90%) monocytes, and a lower pDC (1.19% vs. 12.01%) and monoDC (1.98% vs. 6.80%) in EV-A71 infected severe HFMD patient. Dynamic analysis of PBMCs infected with EV-A71 isolates (mild, moderate and severe) and cell trajectory analysis indicated during infection, monocyte/macrophages were initially activated, followed by three groups of T cells and NK and B cells, M1 macrophage. High concentration of EV-A71 infected macrophage supernatant inhibited SH-SY5Y cell proliferation. ENSG00000285779, TICAM2, RPL13AP26 and HNF4G are significantly different in EV-A71 or inactivated EV-A71 infected macrophages than in control. ENSG00000264324, ENSG00000260643, ISLR2, CCR7, TENM4, INO80B-WBP1, BLOC1S5-TXNDC5 are potential genes about direct virus damage or viral RNA recognition in macrophages. GO annotation and KEGG analysis indicate that EV-A71 infection cause the changes of neural receptor-ligand binding pathway, activation of specific immunity, calcium signaling pathway, and cell aggregation.ConclusionsMacrophages are activated early during EV-A71 infection, thus initiating specific immunity, which is closely related to the severe HFMD. The nerve damage pathway and calcium signaling pathway caused by EV-A71 virus infection of macrophages deserve to more attention.